2021
DOI: 10.3390/pathogens11010018
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for an Association between Previous HEV Genotype-3 Exposure and Glomerulonephritis in General

Abstract: Among numerous other immune-mediated diseases, glomerulonephritis has also been suspected to be an extrahepatic manifestation of HEV infection. In this prospective study, we tested 108 patients with glomerulonephritis and 108 age- and sex-matched healthy controls at the University Hospital Hamburg Eppendorf, Hamburg, Germany, for anti-HEV IgG (Wantai test) as a marker for previous HEV exposure. A total of 24 patients (22%) tested positive for anti-HEV IgG. Males tended to be more frequently anti-HEV IgG positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Furthermore, Taton et al reported that HEV infection was the causative agent of de novo membranous nephropathy that developed in a patient who underwent kidney transplantation [ 38 ]. On the other hand, Pischke and colleagues reported that past exposure to HEV-3 infection in German patients was not linked to the development of GN in general but could link to membranoproliferative glomerulonephritis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Taton et al reported that HEV infection was the causative agent of de novo membranous nephropathy that developed in a patient who underwent kidney transplantation [ 38 ]. On the other hand, Pischke and colleagues reported that past exposure to HEV-3 infection in German patients was not linked to the development of GN in general but could link to membranoproliferative glomerulonephritis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that exposure to HEV could be a risk factor for renal complications such as GN. On the other hand, Pischke and colleagues reported that the percentages of anti-HEV IgG among GN and healthy subjects were 22% and 29%, respectively, in regions endemic to HEV-3 [ 11 ]. Since there were no significant differences in HEV seropositivity between both groups, the authors hypothesized that there was no link between past HEV-3 exposure and GN development in general [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glomerular HEV ORF2 protein depositions might have been an aggravating factor. Nevertheless, it is conceivable that in addition to cases of fully developed glomerulonephritis 6,[9][10][11] , as in patient 1, glomerular damage associated with more subtle HEV-ORF2 protein deposits, as in patients 2-4, may represent a general early morphological correlate and harbinger of impaired glomerular function in the context of HEV infection.…”
mentioning
confidence: 99%